The amounts of logging residues and stump and root wood technically harvestable in southeast Finland - Mäkelä, Markku (Silva Fennica, 1977)
The amounts of harvestable logging residues and stump and root wood were examined in the area where 100,000 solid m of stemwood was cut in 1975. The cutting amounts of stemwood from work sites suitable for harvesting of logging residues was 35,000 m, and suitable for harvesting of stump and root wood 38,000 m. The increase in the yield of wood (without bark) from logging residues compared with the unbarked stemwood was 2.4%. The same percentage of wood from stump and root wood was 5.0â5.8% depending on the harvesting loss.333